Dual Blockade of Inhibitory Immunoreceptors TIGIT and PD-1 Produces Optimal Synergistic Anti-Tumor Effects - Kramer, Paige (Midwestern Journal of Undergraduate Sciences, 2022)
Recent investigation into immunoregulatory roles of both TIGIT and PD-1 T cell receptors reveals that their suppressive effects converge with the inhibition of another T cell receptor, CD226. Co-blockade of these receptors reduced tumor volume in vivo and shows potential as a promising new cancer immunotherapy.